(untitled) (Polifonia, 2002)
ABSTRACT: The peculiarity of the Mato-grossense Portuguese (PMB) Phonology is due to the way it organizes some Brazilian Portuguese (PB) sounds and syllables. In this article, the PMB general phonology, vocalic and consonantal phonemes will be described in relation to PB. Although, the main objective of this work is to analise PMB phonological simplification process in the perspective of CV Phonology, one model from Non-Linear Phonologic Theory.